Large and powerful or small and lovely: opinions of first-generation agricultural entrepreneurs on agribusiness success factors - Garima,; Dhingra, Atul; Bishnoi, Dalip K.; Lemma, Habtamu R.; Lamba, Ritu (Frontiers in Sustainable Food Systems, 2023)
India’s economy is based on agriculture, so agricultural entrepreneurship has the potential to boost economic growth, diversify national income, and create many jobs and business opportunities. The goal of this paper, then, is to find out what first-generation agricultural entrepreneurs think about the things that make an agribusiness successful. The data were collected from 22 districts in four geographical zones (East Zone, West Zone, North Zone, and South Zone) in the state of Haryana. Both a 5-point Likert scale and a 7-point semantic differential scale were used to rate the items. The data was looked at using both descriptive statistics and the Friedman nonparametric test. In this study, we found that the majority of first-generation agribusiness owners were men, and they tended to be sole proprietors of small businesses with fewer than 10 employees. The finding also indicates that advanced storage and transportation facilities, market information, product quality, cutting-edge technology, and the careful management of financial resources are the topmost necessities for the successful operation of any agribusiness. The study also found that the size of the firm has a positive and statistically significant impact on the opinions of first-generation agripreneurs on business and production, marketing, competition, and financial and human resource management. The study recommends that policymakers and development agencies should focus on providing support to agripreneurs in terms of infrastructure, market access, and technological advancements. Additionally, efforts should be made to encourage more first-generation agripreneurs to enter the agribusiness sector by providing them with the necessary resources and training.